Methyl-Beta-Cyclodextrin Restores Aberrant Bone Morphogenetic Protein 2-Signaling in Bone Marrow Stromal Cells Obtained from Aged C57BL/6 Mice - Daniel Halloran; Venu Pandit; Kelechi Chukwuocha; Anja Nohe (Journal of Developmental Biology)
During aging, disruptions in various signaling pathways become more common. Some older patients will exhibit irregular bone morphogenetic protein (BMP) signaling, which can lead to osteoporosis (OP)—a debilitating bone disease resulting from an imbalance between osteoblasts and osteoclasts. In 2002, the Food and Drug Administration (FDA) approved recombinant human BMP-2 (rhBMP-2) for use in spinal fusion surgeries as it is required for bone formation. However, complications with rhBMP-2 arose and primary osteoblasts from OP patients often fail to respond to BMP-2. Although patient samples are available for study, previous medical histories can impact results. Consequently, the C57BL/6 mouse line serves as a valuable model for studying OP and aging. We find that BMP receptor type Ia (BMPRIa) is upregulated in the bone marrow stromal cells (BMSCs) of 15-month-old mice, consistent with prior data. Furthermore, conjugating BMP-2 with Quantum Dots (QDot®s) allows effective binding to BMPRIa, creating a fluorescent tag for BMP-2. Furthermore, after treating BMSCs with methyl-β-cyclodextrin (MβCD), a disruptor of cellular endocytosis, BMP signaling is restored in 15-month-old mice, as shown by von Kossa assays. MβCD has the potential to restore BMPRIa function, and the BMP signaling pathway offers a promising avenue for future OP therapies.